Air Dome Acoustics - Trematerra, Amelia; Lombardi, Ilaria; Iannace, Gino (Canadian Acoustics, 2017)
Air dome is an air supported structure, it is a building composed by one or more layers of continuous flexible membrane anchored to the ground, inflated and supported by pressurized air. In the present work are shown results of acoustic measurements inside an air dome. In this type of structure reverberation time values, at the medium frequencies, are over 8 s and therefore with an excessive reverberation is significantly reduced ability to speech understanding that during training phases does not correctly allow to understand the instructions of coaches. With use of a software for architectural acoustics it was evaluated a possible acoustic correction for reducing reverberation time, by introducing into the turned area of air dome some sound absorbing material.